Sequence and organization of the complete mitochondrial genome of Hebius vibakari ruthveni from China. (3rd July 2016) - Xu, Chunzhu; Zhao, Shuai; Han, Xiaomin
Abstract: The mitochondrial genome sequence of Hebius vibakari ruthveni is analyzed and presented for the public for the first time. The genome was 17, 259 bp in length and contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 2 control regions. The overall base composition is A (33.9%), C (26.5%), T (26.5%), and G (13.1%). Mitochondrial genomes analyses based on maximum parsimony (MP), neighbor-joining (NJ), and Bayesian analyses yielded identical phylogenetic trees, indicating a close phylogenetic affinity of the 24 Colubridae species. It shows that two major phyletic lineages were present in Colubridae: Hebius and Thamnophis. Hebius comprised 16 species and was supported by bootstrap values of 99%. A clade ( H. craspedogaster, H. metusium, H. johannis, H. bitaeniatum and H. octolineatum ) as the sister taxon to another clade ( H. parallelum, H. khasiense, H. Boulengeri and H. popei ) was supported by bootstrap values of 66%. This clade with the H. Atemporale is the sister taxon to H. optatum, H. sauteri, and H. v. ruthveni .